Explaining Muslim Americans’ Opinions on Salient Issues - Gasim, Gamal (Islam and Christian-Muslim relations, 2014)
Despite numerous individual success stories of living the American dream, the Muslim American community still remains one of the most misunderstood and underrepresented minorities in the United States. This study investigates the views of this community by mapping and explaining members' investigates on a number of issues of social and political import. It shows that the issue attitudes of Muslim Americans are rather uniform on some social and non-social issues but very diverse on others. Moreover, it also shows that the differences of opinion that were uncovered can be explained by a variety of factors including a respondent's ethnic or national origin and how committed a respondent is to the practice of Islam, defined by the frequency of mosque attendance. While these results are temporally limited, they do show that this is a very diverse community and set a strong foundation for further quantitative and qualitative investigations of how Muslim Americans' religious practices, ethnic backgrounds, and socio-economic characteristics affect their essential social and political beliefs.